A Review of Strategies for Resilience and Healthy Urban Living Environment under the Background of COVID-19 Pandemic - Roosmayri Lovina Hermaputi; Hua Chen (Department of Urban and Regional Planning, Diponegoro University, 2022)
Since the COVID-19 pandemic strikes the global world, our cities are facing severe damage that affects all sectors of human life and their living environment, and it brings severe harm to humans physical and damaging impact on the urban economy and the operation of the urban system. With higher population density, dense space, and polluted urban areas as the main battlefield for pandemics and becoming the epidemic epicenter, a greater risk of virus transmission is more significant, especially person-to-person infection. A living environment is an essential place for people to devour and change nature and entails the physical attributes and the reconciliation of human exercise, which has essential roles in preventing and controlling pandemics. Thus, this study proposes pandemic resilience and a healthy urban living environment as the suitable future urban living environment concept. Reviewing available published literature related to resilient and healthy urban living environment studies during COVID-19 pandemic becomes the only method applied in this study. Starts by reviewing the concept of the healthy and resilient urban living environment, presenting the experience of Chinese cities facing the pandemic, and providing the urban living environment's potential strategies reflecting healthy and resilience comprehensively through evaluating recent ideas and trends. It aims to answer the research question to find the potential strategies to create pandemic resilience and a healthy urban living environment.